The predictive value of anti-Müllerian hormone on embryo quality in PGT-A cycles analysis - Ni, Mengxia; Zhang, Haoting; Sun, Jian; Zhu, Gengchao; Xing, Shiyu; Zheng, Aiyan; Pu, Yan; Liao, Guizhi; Ding, Jie; Meng, Qingxia; Li, Hong; Fei, Jia; et al. (Frontiers in Endocrinology, 2025)
ObjectiveAlthough anti-Müllerian hormone (AMH) is a well-established predictor of oocyte number in assisted reproduction (ART) applications, its potential to reflect embryo quality in ART cycles remains uncertain. This study explored the association between AMH levels and embryo quality, using aneuploidy rates from preimplantation genetic testing for aneuploidy (PGT-A) as an objective indicator of embryo quality.MethodsA retrospective analysis was performed on patients (excluding those with male factor infertility) who underwent PGT-A at the Reproduction and Genetics Center of Suzhou Municipal Hospital (2018-2022). Patients were stratified by age (<35, 35-37, ≥38 years), body mass index (BMI) (<18.5, 18.5-25, ≥25 kg/m²), number of viable embryos (1-2, 3-4, ≥5), and AMH levels. Group comparisons used independent samples t-test, and correlations with embryo quality were analyzed via logistic regression.ResultsIn 542 PGT-A cycles, AMH levels, euploidy and mosaicism rates negatively correlated with age, while, aneuploidy rates were positively correlated with age. BMI group showed AMH levels shows no significant differences between the groups. However, there were significant differences in euploid, aneuploidy rates among the BMI groups(≥25 kg/m²vs <18.5 kg/m²; 18.5–25 kg/m²vs <18.5 kg/m²). Both AMH levels and euploidy rates were positively correlated with the number of viable embryos, while the aneuploidy rate was correlated negatively. The>1.68 ng/mL AMH group had significantly higher euploidy and lower aneuploidy rates. AMH levels negatively correlated with aneuploidy rates.ConclusionAMH levels serve as a valuable predictor of embryo quality, with the >1.68 ng/mL group showing better quality than the ≤1.68 ng/mL group. AMH levels strongly correlate with female age and the number of biopsy embryos but not BMI. Embryo quality demonstrated a significant decline with increasing female age and a marked improvement with a higher number of biopsy embryos and higher AMH levels. BMI did not linear correlation with embryo quality, thus cannot be considered an independent predictor of embryo quality.